PERLUNYA KEADILAN RESTORATIF DALAM SISTIM PERADILAN ANAK TERHADAP KENAKALAN REMAJA - Wandi Subroto (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
Children and adolescents are the nation's most important assets, and they must be protected from harmful influences that might lead to juvenile delinquency, which leads to criminal activities, and punishment by the law. In Indonesia, a crime is punished according to the court's ruling. If done to children or teenagers, it can lead to negative stigma and discrimination that can impact their future development. For this reason, other approaches to child-related legal cases, such as restorative justice, must be considered. As a result, this study seeks to assess the impact of restorative justice in Indonesian juvenile courts. The research method used is normative juridical legal research, and the research strategy is legal. Secondary data sources include literature and document investigations. The research concluded that diversion is one of the alternatives for addressing legal issues outside of court, as stated in Law No. 11 of 2012 about the Juvenile Justice System, stressing deliberation among perpetrators, victims, families, and connected parties. Recovery, not vengeance, is the aim.